Application of carbon dots synthesized from tryptone and yeast extract in bioimaging and highly selective detection of p-nitrophenol and nickel(ii). Issue 44 (29th October 2019) - Qin, Kunhao; Zhang, Dongfang; Ding, Yafang; Zheng, Xiaodan; Tan, Wenzhang; Xiang, Yingying; Hua, Jianhao; Ji, Xiuling; Li, Bo; Wei, Yunlin
Abstract : Carbon dots (CDs) possess properties appropriate for application in various fields, especially in environmental pollution detection and biological imaging. Abstract : Carbon dots (CDs) possess properties appropriate for application in various fields, especially in environmental pollution detection and biological imaging. With the unprecedented worsening of environmental quality, rapid identification and real-time monitoring of toxic compounds are very important. We successfully synthesized fluorescent CDs doped with tryptone and yeast extract via a hydrothermal process. The readily procured CDs-TY possess good photostability and can be applied as a probe for highly selective, rapid, and facile detection of both p -nitrophenol ( p -NP) and Ni 2+ . The prepared CDs-TY display an excellent linear response to the concentrations of p -NP and Ni 2+ in the range of 0.03–20 μM and 0.1–32 μM, respectively. The limit of detection (LOD) for p -NP was as low as 12 nM, which is lower than most reported values thus far. Additionally, HeLa cells and microbial cells were employed to explore the application of CDs-TY in bioimaging in vitro . CDs-TY exhibit excellent biocompatibility, and can be employed as fluorescent imaging dyes for the visualization of microbial (both live and dead) and HeLa cells. Interestingly, we also clearly observed that CDs-TY had no adverse effect on the growth and reproduction of microbes, which provides strong evidence regarding the biosafety of CDs-TY.